Chronic idiopathic thrombocytopenia treated with immunoglobulin. Issue 11 (November 1983) - Mori, P G; Mancuso, G; del Principe, D; Duse, M; Miniero, R; Tovo, R; Bardare, M; Carnelli, V; de Mattia, D
Abstract : Twenty five children with chronic idiopathic thrombocytopenic purpura followed from 6-96 months in 7 Italian paediatric departments were treated with high dose immunoglobulin according to a multicentre protocol. Positive responses were observed in 20 of 25 patients (80%) and negative responses in 5 of 25 (20%). On previous steroid treatment 7 of 10 positive responders were steroid resistant and 13 of 15 were steroid dependent. Within four weeks of beginning treatment 16 of 20 patients (80%) relapsed, while 4 of 20 (20%) maintained normal platelet values after 4-12 months' follow up. Statistical analysis of the platelet count on day five of treatment enabled us to divide positive responders into three groups: good, intermediate, and poor. The possible mode of action and clinical application of high dose immunoglobulin are discussed.